Study of functional outcome of total hip arthroplasty in a series of cases of hip pathologies done in rural population - Kadam, Rahul; Bansal, Pankaj; Chhallani, Abhay (International Journal of Research in Orthopaedics, 2016)
Background: The objective of the study was to assess the functional outcome of total hip arthroplasty (THA) done in a series of cases of hip pathologies rural population. Methods: A retrospective randomized controlled study conducted in 50 cases of hip arthritis (38 males and 12 females) treated with uncemented THA for an average follow-up of 2 years at department of orthopedics MGM Medical College, Kamothe, Navi Mumbai. Harris hip scoring system was used for the functional scoring and the postoperative radiographs were assessed by Gruen zones for the femoral component and DeLee and Charnley zones for the acetabular component. All patients were evaluated pre operatively and post operatively 3 months 6 months, 12months, 2years with Harris Hip score. Results: 81% of our patients scored 85 points or better for a rating of excellent by Harris hip score system. 90% patients had little /no pain post operatively, whereas walking ability improved and was unlimited in 80% of the patients post operatively. Harris hip score improved from 40 to 80. 80.5% -excellent, 13.80% -good, 5.7% -fair results. Poor results were not seen in any patient. Conclusions: THR provided excellent pain relief, adequate stability, and remarkable range of motion in severely painful, refractory hip. A significant improvement was seen at two year follow-up.